Civil society organisations’ responses to the effects of the Coronavirus disease (COVID-19) pandemic in Ghana - Solomon Kofi Amoah (Journal of Government and Civil Society, 2022)
Globally, civil society organisations (CSOs) operate in uncertain environments. Thus, resilient CSOs have a demonstrable ability to turn challenges into opportunities. The literature highlights how some CSOs successfully adapt to external threats to their existence. However, how the coronavirus (COVID-19) pandemic has affected the operations of CSOs in Ghana and how these organisations are responding to the effects has received very little empirical attention and documentation. This paper examines the impact of the COVID-19 pandemic on CSOs’ operations and the strategic responses of these organisations. It draws on evidence collected in Ghana through qualitative and quantitative approaches. The paper argues that while the impact of the pandemic on CSOs was dramatic in the short to medium term, CSOs’ resolve to ensure that they remain relevant to critical stakeholders, including mainly their intended beneficiaries and donors, has been their most vital survival anchor. Secara global, organisasi masyarakat sipil (NGO) beroperasi di lingkungan yang tidak pasti. Dengan demikian, NGO yang tangguh memiliki kemampuan yang dapat dibuktikan untuk mengubah tantangan menjadi peluang. Berbagai literatur telah menyoroti bagaimana beberapa NGO berhasil beradaptasi dengan ancaman eksternal terhadap keberadaan mereka. Namun, bagaimana pandemic virus corona (COVID-19) telah memengaruhi operasi NGO di Ghana dan bagaimana organisasiorganisasi ini merespons dampaknya, hanya mendapat sedikit perhatian dan dokumentasi empiris. Studi ini mengkaji dampak pandemi COVID-19 terhadap operasi NGO dan respons strategis organisasi organisasi tersebut. Ini mengacu pada bukti yang dikumpulkan di Ghana melalui pendekatan kualitatif dan kuantitatif. Studi ini berpendapat bahwa sementara dampak pandemic pada NGO sangat dramatis dalam jangka pendek hingga menengah, tekad NGO untuk memastikan bahwa mereka tetap relevan dengan pemangku kepentingan, termasuk terutama penerima manfaat dan donor yang dituju, telah menjadi jangkar kelangsungan hidup mereka yang paling vital.